THE EFFECTIVENESS OF CHILD SUPPORT ENFORCEMENT THROUGH THE APPLICATION OF KHI ARTICLE 156 - Taufika Hidayati (ASIAN PUBLISHER, 2026)
KHI Article 156 firmly obligates the father to bear all child maintenance costs after divorce, yet this rule is weak at the enforcement level due to two main structural deficiencies, the absence of direct sanctions for violations and the lack of an active post-verdict monitoring mechanism. This normative juridical study aims to identify the normative weaknesses of KHI Article 156 and to formulate legal solutions that can strengthen its enforcement. The analysis was conducted through a statutory approach and a conceptual approach to relevant primary and secondary legal materials. This study found that these normative weaknesses are compounded by an execution mechanism that burdens the mother and a misconception about Batak customary law that shifts maintenance responsibility from the father to the mother; the mother's legal literacy regarding execution channels is also still very low. This study recommends the issuance of a PERMA regulating a model of progressive sanctions and active monitoring of maintenance verdicts, supported by a digital tracking along with the integration of mediation based on Batak customary values as an alternative enforcement pathway.